Platelets as Key Factors in Inflammation: Focus on CD40L/CD40 - Cognasse, Fabrice; Duchez, Anne Claire; Audoux, Estelle; Ebermeyer, Theo; Arthaud, Charles Antoine; Prier, Amelie; Eyraud, Marie Ange; Mismetti, Patrick; Garraud, Olivier; Bertoletti, Laurent; Hamzeh-Cognasse, Hind (Frontiers in Immunology, 2022)
Platelets are anucleate cytoplasmic fragments derived from the fragmentation of medullary megakaryocytes. Activated platelets adhere to the damaged endothelium by means of glycoproteins on their surface, forming the platelet plug. Activated platelets can also secrete the contents of their granules, notably the growth factors contained in the α-granules, which are involved in platelet aggregation and maintain endothelial activation, but also contribute to vascular repair and angiogenesis. Platelets also have a major inflammatory and immune function in antibacterial defence, essentially through their Toll-like Receptors (TLRs) and Sialic acid-binding immunoglobulin-type lectin (SIGLEC). Platelet activation also contributes to the extensive release of anti- or pro-inflammatory mediators such as IL-1β, RANTES (Regulated on Activation, Normal T Expressed and Secreted) or CD154, also known as the CD40-ligand. Platelets are involved in the direct activation of immune cells, polynuclear neutrophils (PNNs) and dendritic cells via the CD40L/CD40 complex. As a general rule, all of the studies presented in this review show that platelets are capable of covering most of the stages of inflammation, primarily through the CD40L/CD40 interaction, thus confirming their own role in this pathophysiological condition.